Use Of Zakat Logo In Optimizing Corporate Zakat Collection In Malaysia Towards Shared Prosperity Vision 2030 - Azman Ab Rahman; Afaf Sukari; Setiyawan Gunardi; Syed Mohd Najib Syed Omar (Seybold Publications, 2024)
Volume : 18 No: 12